The Structure of Entrepreneurial Team Members' Competencies: Between Effectuation and Causation - Katarzyna Stankiewicz; Michał T. Tomczak; Paweł Ziemiański; Beata Krawczyk-Bryłka (MDPI AG, 2020)
A conscious shaping of entrepreneurial competence is a relevant element of entrepreneurial education. In order to recognize which of the competencies regarded as entrepreneurial are characteristic of members of entrepreneurial teams, which is crucial for the work of those teams, it is necessary to identify the structure of those competencies. This quantitative study was conducted with the use of a survey method and involved 111 entrepreneurs working within 48 entrepreneurial teams. The main objective of the research was to verify the compliance of entrepreneurial competence with the effectual vs. causal approach, which would allow us to answer the question regarding which of these approaches characterizes entrepreneurs to a greater extent. This study aimed to examine which entrepreneurial competencies characterize entrepreneurs working in entrepreneurial teams, to verify them with the effectual vs. causal approach, and to define their internal structure. The results of this research revealed that the competencies related to the effectual approach are indicated to more frequently and strongly characterize the surveyed entrepreneurs. Additionally, an exploratory factor analysis enabled the identification of three main, internally consistent groups of elements forming the competence structure of the surveyed entrepreneurs. Our results may be used in the development and modernization of curricula and courses in entrepreneurship education.